HUKUM ANJURAN TERTULIS MEDIATOR DALAM PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL (pasca Putusan Mahkamah Konstitusi No. 68/PUU-XIII/2015) - Aprilina Rahmah Yusticia (Universitas Muhammadiyah Ponorogo, 2023)
This study aims to analyze how the legal force of written recommendations on settling industrial relations disputes was issued by mediators after the Constitutional Court Decision Number: 68/PUU-XIII/2015. The type of research used in this research is normative research or doctrinal research. And the approach used to answer the problem is the Legislative Approach (Statute Approach). This research is motivated by the application of Judicial Review by several workers to the Constitutional Court on the word 'recommendation' in Article 13 paragraph (2) letter a and Article 23 paragraph (2) letter an of Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes. The results of this study indicate that the settlement of industrial relations disputes through mediation is mandatory, starting from the decision of Constitutional Court Number: 68/PUU-XIII/2015. Written recommendations are seen as part of industrial relations dispute settlement minutes. The Petitioner's application for the word